Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.jpeds.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Severe Acute Respiratory Syndrome Coronavirus 2 Detection on Breastfeeding Due to Infant Separation at Birth

Abstract: Objective To assess the impact of separation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) polymerase chain reaction (PCR)-positive mother-newborn dyads on breastfeeding outcomes. Study design This observational longitudinal cohort study of mothers with SARS-CoV-2 PCR-and their infants at 3 NYU Langone Health hospitals was conducted between March 25, 2020, and May 30, 2020. Mothers were surveyed by telephone regarding predelivery feeding plans, in-hospital feeding, and home feeding of their n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 12 publications
6
50
1
6
Order By: Relevance
“…During a 5-week period (July 15–August 20) when many areas of the country were experiencing substantial community transmission of SARS-CoV-2, hospitals were implementing a variety of practices intended to balance evidence-based maternity care with COVID-19-related IPC. Hospital practices are likely evolving along with the pandemic ( 7 ), potentially driven by multiple factors, including level of community transmission, guidance from public health and medical professional organizations, and a hospital’s own experience in preparation for or caring for pregnant women and newborns with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During a 5-week period (July 15–August 20) when many areas of the country were experiencing substantial community transmission of SARS-CoV-2, hospitals were implementing a variety of practices intended to balance evidence-based maternity care with COVID-19-related IPC. Hospital practices are likely evolving along with the pandemic ( 7 ), potentially driven by multiple factors, including level of community transmission, guidance from public health and medical professional organizations, and a hospital’s own experience in preparation for or caring for pregnant women and newborns with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…One third of hospitals in this study reported not having cared for any neonates born to mothers with COVID-19; however, others had extensive experience, including 17 hospitals reporting caring for at least 100 of these newborns. Follow-up of mothers with COVID-19 delivering at three large New York birth hospitals found reduced breastfeeding rates both in the hospital and after returning home among mothers who had been separated from their newborns ( 7 ). After identification of this finding, and the observed stress among mothers and newborns as a result of separation, the hospital system revised its policy and began to allow asymptomatic mothers with laboratory-confirmed COVID-19 to room-in and breastfeed.…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to successfully breastfeed may never recover, an obvious harm with longterm effects, manifesting initially by decreased initiation, exclusivity, and duration. 49 The absence of recommendations for psychological support for separated mothers and infants in the vast majority of guidance is alarming and cannot be justified on the basis of infection control risk. 50 Physical distance between mothers and infants and lack of breastfeeding undermine maternal caregiving capacity and place infants at increased risk of poor developmental and psychological outcomes, abuse and neglect.…”
Section: Discussionmentioning
confidence: 99%
“…One study estimated the negative effects of separation on breastfeeding both in-hospital and after discharge. 22 The American Academy of Pediatrics (AAP) perinatal COVID-19 registry published online data about the safety of rooming-in and direct breastfeeding in July and October, with >3,500 mother/infant dyads, but did not include specifics about infant distance from the mother. 23 In July and August 2020, data were published by 2 metropolitan New York hospitals that practiced rooming-in, skin-toskin care, and direct breastfeeding, each with very different transmission rates (0% and 6.7%).…”
Section: Introductionmentioning
confidence: 99%